2023
DOI: 10.1038/s41586-023-05776-4
|View full text |Cite
|
Sign up to set email alerts
|

Tracking early lung cancer metastatic dissemination in TRACERx using ctDNA

Abstract: This is a repository copy of Tracking early lung cancer metastatic dissemination in TRACERx using ctDNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(59 citation statements)
references
References 61 publications
3
56
0
Order By: Relevance
“…These results suggest that, at the time of surgical resection, clones with metastatic potential were more likely to have undergone a subclonal expansion within the primary tumour. A similar phenomenon was found in the accompanying Article using circulating tumour DNA to track metastatic disease 19 .…”
Section: Selection In Metastasessupporting
confidence: 70%
See 1 more Smart Citation
“…These results suggest that, at the time of surgical resection, clones with metastatic potential were more likely to have undergone a subclonal expansion within the primary tumour. A similar phenomenon was found in the accompanying Article using circulating tumour DNA to track metastatic disease 19 .…”
Section: Selection In Metastasessupporting
confidence: 70%
“…We also found that polyclonal dissemination at the case level was associated with extrathoracic disease recurrence. In the accompanying Article, we noted that polyclonal dissemination as identified by analysis of circulating tumour DNA, was associated with poor overall survival outcomes 19 . The increased diversity associated with polyclonal dissemination may enable more rapid adaptation to extrathoracic environmental niches and subsequent heterogeneous treatment responses between metastases, providing a possible mechanism accounting for this survival difference.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results from the characterization of the project cell line panel by whole exome sequencing and from the determination of drug sensitivity profiles both indicated that cancer cell resistance formation is a complex, individual, and unpredictable process. This finding is in agreement with data from studies, in which cancer cell lines were repeatedly adapted to the same drug in independent experiments 17,48,49 and with recent findings from the comprehensive analysis of cancer cell evolution in lung cancer patients 5054 .…”
Section: Discussionsupporting
confidence: 92%
“…An initial characterization by whole exome sequencing in combination with patient-derived TCGA data resulted in the identification of 135 biomarker candidates for the guidance of personalized TNBC therapies for further investigation, including 58 ones that are novel and had not been associated with drug resistance in cancer before. Finally, whole exome data and drug sensitivity profiles showed that each cancer cell line adaptation process follows an individual, unpredictable route, which reflects recent clinical findings from the monitoring of cancer cell evolution in patients 5054 . This further supports the relevance of drug-adapted cancer cell lines as preclinical models of acquired resistance that can be analyzed and manipulated at a level of detail that is impossible in the clinical setting.…”
Section: Discussionsupporting
confidence: 69%
“…Two in silico approaches were used to more precisely describe the specificity of the assay, the method of Abbosh et al (2023) [45] that draws on loci flanking each targeted site and an internally developed method relying on somatic variant target reshuffling (see materials and methods). These analyses each resulted in 23,600 in silico panels with the detection of 4 and 31 false positives, respectively, giving measured specificities of 99.98% (95% CI 99.96% to 100.00%) and 99.95% (95% CI 99.92% to 99.98%).…”
Section: Resultsmentioning
confidence: 99%